Possible Involvement of Intracellular Calcium-Independent Phospholipase A2 in the Release of Secretory Phospholipases from Mast Cells—Increased Expression in Ileal Mast Cells of Crohn’s Disease - Ulrika Christerson; Åsa V. Keita; Martin E. Winberg; Johan D. Söderholm; Christina Gustafson-Svärd (Cells, 2019)
Increased activity of secretory phospholipases A2 (sPLA2) type-II was previously observed in ileum of Crohn’s disease (CD). Our aims were to explore the involvement of calcium-independent (i)PLA2β in the release of sPLA2s from the human mast cell (MC) line (HMC-1) and investigate expressions of cytosolic (c)PLA2α, iPLA2β, sPLA2-IIA and sPLA2-V in MCs of CD ileum. The release of sPLA2 was investigated in HMC-1 by immunocytochemistry and ELISA. The expression intensities of PLA2s in mucosal MCs, and the proportion of PLA2-positive MCs, were investigated in normal ileum and in ileum from patients with CD by immunohistochemistry. The calcium ionophore-stimulated release of sPLA2-IIA and sPLA2-V from HMC-1 was reduced by the iPLA2-inhibitor bromoenol lactone. All four PLA2s were detectable in mucosal MCs, both in normal ileum and in CD, but the proportion of iPLA2β-containing mucosal MCs and the expression intensity of sPLA2-IIA was increased in CD. Results indicate that iPLA2β is involved in the secretion of sPLA2s from HMC-1, and suggest that iPLA2β-mediated release of sPLA2 from intestinal MCs may contribute to CD pathophysiology. Ex vivo studies on isolated mucosal mast cells are however needed to clarify the precise role of MC PLA2s in the inflammatory processes of CD.